"Don't Make the Gap" Surgical Technique and Case Series for Chronic Achilles Rupture. Issue 4 (December 2021) - Arthur, Jacob M.; Venrick, Connor B.; Ryan, Paul M.
Abstract : Chronic Achilles tendon ruptures continue to be difficult conditions to treat, with no gold standard surgical procedure agreed upon. There are many previously described techniques for treating chronic rupture; however, these typically include excision of the interposed scar tissue. This study describes a technique that avoids resection of this scar tissue that allows for maximum final tendon length without the risk of gap formation. In addition, this study reports a case series of 7 patients who underwent the described technique at an average of 30 weeks after injury. These patients were followed-up for an average of 36 months, with similar outcome scores as shown in previous literature. This series demonstrates that good surgical outcomes are attainable while avoiding scar excision for patients with chronic Achilles tendon ruptures. Level of Evidence: Diagnostic Level III. See Instructions for Authors for a complete description of levels of evidence.